Erosion, Sediments Transport and Riverbank Stability: A Review. Issue 1 (August 2020) - Aldefae, Asad H.; Al-Khafaji, Rusul A.; Shamkhi, Mohammed S.; Kumar, Haider Q.
Abstract: This paper is a review of the basic theoretical information needed to understand the riverbank stability, failure mechanism, and its causes. The first part describes the basic principles of river systems involving river hydraulics, sediment load, and channel morphology. This is pursued by a brief discussion concerning riverbank erosion that involves theoretical equations and numerical methods to quantify erosion. Finally, an in-depth discussion concerning riverbank stability that involves the types of failure mechanism, tension cracks, and riverbank settlement is conducted. Also, the paper reviews some previous studies on riverbank stability.